Dynamic electroencephalographic study of persons – mild COVID-19 convalescents - S. A. Gulyaev (Русский журнал детской неврологии)
Background. The term “postcovid syndrome” is firmly entrenched in medical terminology, but many aspects of its clinical manifestations are not well understood.   Aim. To establish the presence of the nature and severity of changes in the bioelectrical activity of the brain in COVID-19 survivors, as well as their relationship with the formed clinical neurological and neuropsychological syndromes during convalescence.   Materials and methods. A dynamic study was conducted of 38 COVID-19 survivors returning to work. Neurophysiological studies were carried out using the EGI-GES-300 system (128 channels). The descriptive characteristics of electroencephalograms were built on the method of studying the spectral density of the electroencephalographic signal on the surface of the scalp, and the dynamic characteristics of the signal were studied by fixing electroencephalographic microstates, using the method of D. Lemmon and T. Kenning.   Results and conclusions. In the study, a relatively new diagnostic technique for studying cognitive impairments based on the analysis of electroencephalographic microstates was implemented, which made it possible to identify signs of functional restructuring of the neuronal macronetworks of the brain and trace the characteristic adaptation of a person during the period of convalescence.